PENCEGAHAN HIV DAN AIDS MELALUI KURSUS PRA NIKAH DALAM PERSPEKTIF ISLAM DAN SAINS - Ahmad Zubaeri; Mutista Hafshah (UIN Walisongo Semarang, 2022)
The HIV epidemic has been present in Indonesia for the past twenty years, despite various prevention efforts. However, the trend is very concerning, so it is critical to innovate in the prevention of HIV-AIDS, particularly through sexual transmission, as the rate of increase is very rapid. One way to avoid it is to raise a sakinah family, which instills a sense of mutual loyalty to a partner. Pre-marital courses can help to start the development of a sakinah family. The purpose of the pre-wedding course is to provide young people of marriageable age and brides-to-be with knowledge, understanding, skills, and awareness-raising about domestic and family life. This pre-wedding course is a three-day, 24-hour briefing (shot course) for teenagers of marriageable age or prospective brides. Teaching and learning facilities for organizing pre-marital courses include syllabus, modules, and other teaching materials required for learning. The syllabus and modules prepared by the Ministry of Religion for pre-marital course organizers can be correlated with material on HIV and the importance of Counseling and Testing on Health Officer Initiation (KTIP) and Voluntary Counseling and Testing (KTS), both of which are critical components in efforts to prevent HIV transmission. Furthermore, it can deepen material that synergizes with the purpose of marriage, namely forming a sakinah family and avoiding HIV, namely option B (Be Faithful), meaning being mutually loyal to one sex partner, and if the test result is positive, you can still get married then use option C (Condom).